Ozone Ice as an Oxygen Release Reagent for Heap Leaching of Gold Ore - Ziyuan Liu (MDPI AG, 2021)
The issue of poor aeration efficiency and low oxygen transfer in the heap leaching of gold has gained considerable attention. In this study, ozone ice was studied as an oxygen release reagent in the cyanide heap leaching of gold at a low temperature of approximately 5 °C, owing to its effective oxidation and clean and green properties. Quartz Crystal Microbalance with Dissipation (QCM-D) was used to monitor the effect of different ratios of cyanide and oxygen concentrations on the gold leaching rate. The results showed that the leaching rate doubled when the dissolved oxygen (DO) was increased from 8.2 mg/L to 12 mg/L at a relatively high cyanide concentration of 60 mg/L. The release of oxygen during the process of ozone ice melting was analyzed by simulating the oxygen-deficient condition of the ore heap in column leaching. In the first stage of ice melting, the DO in the solution increased dramatically, and the rate of increase improved with increased initial ozone concentration in the ice. In the second stage of ice melting, the rate of increase in the DO of the solution was not significantly affected by the initial ozone concentration in the ice; this was consistent with the decomposition rate of ozone. The addition of ozone ice containing 300 mg/L ozone increased the gold extraction by 4.1% in the ore column leaching experiment, compared to a column with no ozone ice. However, continuously increasing the ozone concentration up to 600 mg/L had no further significant effect, because the dissolved oxygen in the leaching solution reached saturation. The results facilitate a better understanding of the decomposition law of ozone in the melting process of ozone ice and help to improve the oxygen deficit state in gold leaching heaps.